Avaliação do grau do dano das estruturas do subsolo de três edifícios situados na Região Metropolitana do Recife - Lemos, Sérgio Pereira Pinto (2006)
This work aims to evaluate the pathology of residential buildings structures located at the Metropolitan Region of Recife, Brazil using the quantification of damages to measure the degree of early deterioration of reinforced concrete. Three residential buildings (RB) with similar construction standards were studied. All buildings have approximate age and are inserted into environmental aggressiveness distinct. A visual inspection took place as well as a laboratorial sample analysis of their pillars, beams and underground water reservatories. It was verified that the RB1 case, located at a high environmental aggressiveness class (III), and the RB2 case, located significatively far from the sea and classified with a moderate environmental aggressiveness class (II), both presented a medium degree of deterioration (GDE). For both buildings it is suggested a periodic inspection recommendation and a medium term intervention (GD 1 = 36,98 ; GD 2 = 31,23). The third case (RB3), located at a high environmental aggressiveness class (III) and seafront with protection barriers, presented a high degree of deterioration (GD 3=103,94). It is suggested for RB3 an immediate intervention with collapse risks